Juggling Defense and Security in the Americas: Academic, Diplomatic, and Professional Engagement at the Inter-American Defense College - Hamilton, Mark (Hemisferio - Revista del Colegio Interamericano de Defensa, 2016)
This article examines the juggling act central to defense and security education in the Americas and explores the difficulty of “keeping all the balls in the air” to balance diverse political and professional interests in a complex inter-agency and international environment. The InterAmerican Defense College (IADC), located in Washington DC and operating under auspices of the Organization of American States (OAS) and Inter-American Defense Board (IADB), juggles these tensions daily as it prepares senior military, police, and civilian officials from OAS member nations to serve as strategic advisors on hemispheric defense and security matters. Forced to evolve in the changing regional landscape of the post-Cold War era, IADC has maintained relevance by prioritizing academic improvements and providing unique opportunities for knowledge sharing and relationship-building among future decision-makers of the Americas. This article analyzes some of the competing organizational priorities of IADC and offers an insider view of College outcomes and complex institutional challenges. Case lessons from the IADC experience are framed in a broader regional context, with critical reflections for the evolving field of international military and diplomatic education.